Budget 2016 : perception of rural people in Bongawan / Razdey Ruslin and Khairun Syazwan Maharup - Ruslin, Razdey; Maharup, Khairun Syazwan (2016)
All citizens in Malaysia want a satisfying annual budget that can basically help us in our daily life. It is important for us to get the full access towards Malaysia's annual budget since it is about our welfare. Then, we can have our own perception towards the budget itself. The study was conducted to study the perception of people in rural area towards Malaysian Budget 2016: a case study at Bongawan. The objectives of this study are to determine the rural people perceptions in Bongawan toward Malaysian Budget 2016 and to identify the difference of rural people perceptions in Bongawan based on age, ethnicity, academic background, and employment status. A purposive sampling technique of 200 respondents was selected to answer the questionnaires about the perception of Budget 2016. Data was analysed through descriptive analysis and the data is then describing the normality, frequency, mean and one-way ANOVA. Most of the respondents have a good perception towards the budget allocation and budget priorities. In fact, almost all respondents have a good perception towards the general perception of Budget 2016. It is important for the government to realize the important to the perception of the people especially those in the rural areas so that they can continuously improve their services towards the people.